Peak power: A severity measure for head acceleration events associated with suspected concussions - Tierney, G.; Tucker, R.; Tooby, J.; Starling, L.; Falvey, É.; Salmon, D.; Brown, J.; Hudson, S.; Stokes, K.; Jones, B.; Kemp, S.; O`Halloran, P.; et al. (Sports Medicine, 2026)
Objectives: In elite rugby union, suspected concussions lead to immediate removal from play for either permanent exclusion or a temporary 12-min assessment as part of the Head Injury Assessment 1 (HIA1) protocol. The study aims to retrospectively identify a head acceleration event (HAE) severity measure associated with HIA1 removals in elite rugby union using instrumented mouthguards (iMGs). Methods: HAEs were recorded from 215 men and 325 women, with 30 and 28 HIA1 removals from men and women, respectively. Logistical regression was calculated to identify whether peak power, maximum principal strain (MPS) and/or the Head Acceleration Response Metric (HARM) were associated with HIA1 events compared to non-cases. Optimal threshold values were determined using the Youden Index. Area under the curve (AUC) was compared using a paired-sample approach. Significant differences were set at p < 0.05. Results: All three severity measures (peak power, HARM, MPS) were associated with HIA1 removals in both the men`s and women`s game. Peak power performed most consistent of the three severity measures for HIA1 removals based on paired-sample AUC comparisons in the men`s and women`s games. The HARM and MPS were found to perform lower than peak linear acceleration in the women`s game based on AUC comparisons (p = 0.006 and 0.001, respectively), with MPS performing lower than peak angular acceleration (p = 0.001). Conclusion: Peak power, a measure based on fundamental mechanics and commonly communicated in sports performance, was the most effective metric associated with HIA1 removals in elite rugby. The study bridges the gap by identifying a consistent HAE severity measure applicable across sexes.